Your Moon, My Moon : A Grandmother's Words to a Faraway Child - MacLachlan, Patricia; Collier, Bryan (New York : Simon & Schuster Books for Young Readers, 2011)
Although their homes are different, a grandmother in New England and her loving grandson in Africa share the same moon.
Keywords: Grandmothers -- Fiction; New England -- Fiction; Africa -- Fiction